Properties of Injection Molded Nanocomposites and Blends Based on PLA, PHBV and L-CNC / Martin Borůvka...[et al.] - Borůvka, Martin; Běhálek, Luboš; Habr, Jiří; Lenfeld, Petr; Vácha, Jan; Ngaowthong, Chakaphan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The practical approach to produce sustainable, biobased, biodegradable and ecofriendly blends and nanocomposites with tailored material properties is reported in this paper. The aim of study is to investigate the effect of blending and addition of heterogeneous nucleating agents based on lignin-coated cellulose nanocrystals (L-CNCs) on the properties of poly(lactic acid) (PLA) and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) blends and nanocomposites. The crystallization behaviour, morphology, impact strength and heat deflection temperature of neat PLA, blends and nanocomposites were investigated. Masterbatches were prepared by melt mixing using an internal mixer and further then were standard tensile test bars injection molded. The results showed that both property modifiers (PHBV and L-CNC) had significant influence on PLA material properties. Crystallinity of resulted samples has been improved. Morphology examinations showed PHBV well dispersed in PLA phase in form of droplet like particles in nanometre range. An increase of impact strength and heat deflection temperature (HDT) has been observed.